Introduction to the Pan-Caribbean - Skelton, Tracey, 1962- (Arnold, 2004)
"With its diverse histories of slavery, plantations, colonialism and independence, the Caribbean is richly layered, highly complex and a wonderful example of people's resistance. The pan-Caribbean region also provides an excellent geography through which to understand and analyze the complex processes of globalization, development, migration, tourism, and social and cultural relations. This book is an excellent introduction and is your map through one of the most extraordinary and remarkable parts of the world."--Jacket